2020
DOI: 10.1155/2020/2305784
|View full text |Cite
|
Sign up to set email alerts
|

Resina Draconis Reduces Acute Liver Injury and Promotes Liver Regeneration after 2/3 Partial Hepatectomy in Mice

Abstract: Aim. To investigate the protective effects and possible mechanisms of action of resina draconis (RD) on acute liver injury and liver regeneration after 2/3 partial hepatectomy (PH) in mice. Methods. 2/3 PH was used to induce acute liver injury. Mice were divided into three groups: sham, vehicle + 2/3 PH, and RD + 2/3 PH. Resina draconis was administered intragastrically after 2/3 PH into the RD + 2/3 PH group, and the same volume of vehicle (1% sodium carboxymethyl cellulose) was injected into the vehicle + 2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…ALT is more liver speci c to determine hepatocellular damage 31 . It is reported that these enzymes were increased during partial hepatectomy [32][33][34] . In our study, although there was an increase in ALT, AST, ALP and GGT enzymes in the hepatectomy group compared to the control group, but there was not any statistically signi cant.…”
Section: Discussionmentioning
confidence: 96%
“…ALT is more liver speci c to determine hepatocellular damage 31 . It is reported that these enzymes were increased during partial hepatectomy [32][33][34] . In our study, although there was an increase in ALT, AST, ALP and GGT enzymes in the hepatectomy group compared to the control group, but there was not any statistically signi cant.…”
Section: Discussionmentioning
confidence: 96%
“…ALT is more liver specific to determine hepatocellular damage [31]. It is reported that these enzymes were increased during partial hepatectomy [32][33][34]. In our study, although there was an increase in ALT, AST, ALP and GGT enzymes in the hepatectomy group compared to the control group, but there was not any statistically significant.…”
Section: İnfiltrationcontrasting
confidence: 64%
“…For instance, studies have shown that activating signaling pathways such as HGF, EGFR, and TNF-α prevents acute liver failure and promotes LR. 225 In PHx after cirrhosis, the IL-6 signaling pathway can maintain compensatory LR by enhancing STAT3 activation, 226 the continuous activation of IL-6 signaling pathway can lead to the development of HCC. In mice with carbon tetrachloride (CCl4),-induced cirrhosis, the TGF-β receptor type I(TGFβR1) kinase inhibitor galunisertib (LY2157299) can block the liver fibrosis process and promote LR by inhibiting the TGF-β signaling pathway.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%